Impact of electric vehicle charging station on power quality - Arjun, M. S.; Mohan, N.; Sathish, K. R.; Patil, Arunkumar; Thanmayi, G. (Institute of Advanced Engineering and Science, 2024)
Global warming has led to the widespread adoption of electric vehicles (EV). With the increasing use of electric vehicles, it is very important to understand the impact of electric vehicle charging. Electric vehicle charging station has a serious effect on the power quality of the local power distribution network, and it cannot be ignored. The electric vehicle charger is a type of non-linear load. This non-linearity introduces harmonics into the charging station. Therefore, a high-efficiency charger in the power grid is required. This research work aims to build a charging station model to analyze the effect of EV chargers on power quality and then shunt active power filter (SAPF) based on P-Q theory and synchronous reference frame (SRF). Theory is implemented in the system to suppress harmonics. The simulation will be carried out under two cases, without active power filter (APF) and with APF when number of chargers associated to the charging station. The simulation results of both the methods will be compared and verify the effectiveness of proposed method. The simulation will be done using the MATLAB/Simulink software.